Pengaruh gaya kepemimpinan, loyalitas karyawan terhadap kinerja karyawan - Wibowo, Frendy; Setiyanto, Sigit; Bahtiar, Habib (Journal of Management and Digital Business, 2022)
This study examines the effect of leadership style and employee loyalty on employee performance, where leadership style and employee loyalty are the independent variables, and employee performance is the dependent variable. The population of this study was 53 employees of the Wonogiri Regency DISPORA. Data collection uses populative research methods (Census). The analytical tool used in this study is multiple linear regression analysis. The results showed that leadership style and employee loyalty simultaneously had a positive and significant effect on employee performance.